Tin-silicalite-1: synthesis by dry gel conversion, characterization and catalytic performance in phenol hydroxylation reaction - Niphadkar, Prashant S.; Kotwal, Mehejabeen S.; Deshpande, Shilpa S.; Bokade, Vijay V.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2009)
Tin-silicalite-1 (Sn-MFI) has been successfully synthesized by dry gel conversion (DGC) method. The influence of various synthesis parameters such as crystallization time, temperature, water content at the bottom of autoclave, molar ratios of (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) in dry gel on the crystallization kinetics and physico-chemical properties of Sn-MFI materials has been investigated. Powder-X-ray diffraction (XRD),XPS,AAS, DRUV-vis and SEM techniques were employed as characterization tools. Time-dependent studies revealed that, the progressive crystallization of Sn-MFI depend not only on the synthesis time but also on the other various synthesis parameters. Increase in the crystallization temperature, water content at bottom of autoclave (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) molar ratios in dry gel resulted in the lowering of overall crystallization period. A good correspondence between the chemical composition of the surface and the bulk indicated the uniform distribution of Sn(4+) ions. The presence of these ions in tetrahedral coordination has been indicated by DRUV-vis spectral studies. Although, not better but comparable activity has been shown by Sn-MFI prepared by dry gel conversion method with Sn-MFI prepared by conventional hydrothermal crystallization method in the hydroxylation of phenol reaction. Increase in concentration of isolated Sn(4+) ions led to increase in phenol conversion and H(2)O(2) efficiency. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: crystallisation; Dry gel conversion; microporous materials; Sn-MFI